Optimizing People's Business Credit Distribution with Data Mining at Bank C using the C4.5 Algorithm - Dian, Rahmad; Andesti, Cyntia Lasmi; Sri Restu Ningsih (Cattleya Darmaya Fortuna, 2023)
Customer is the most important asset in a Bank. Possibility of bad credit payments occur in various Banks. Classification of customers of Bank C branch is intended to facilitate the Bank in making decisions in terms of extension credit and in the filing of credit. With the classification of the customer in a Bank, if there is a problem with the same case the Bank is left to see the rules (rules) formed from a decision tree generated. With decision tree decision method using C4.5 algorithm is expected to extract information more quickly and optimally with bigger data capacity, so that errors generated in decision making more minimized. By using Data Mining data processing classification of customers at Bank C Branch becomes easier that is useful to determine the customer is feasible or not given the credit business people at Bank C. The development of this system is done through several stages, the first stage begins with the collection data, the second stage continued with manual data processing, third stage of data processing with the application and the fourth stage of implementation.